Sickle cell disease: wheeze or asthma?. Issue 1 (December 2015) - Cohen, Robyn; Klings, Elizabeth; Strunk, Robert
Abstract Sickle cell disease (SCD) is the most common life-limiting genetic disease among African Americans, affecting more than 100, 000 people in the United States. Respiratory disorders in patients with sickle cell disease have been associated with increased morbidity and mortality. Associations between asthma and pain, acute chest syndrome (ACS), and even death have long been reported. More recently wheezing, even in the absence of an asthma diagnosis, has gained attention as a possible marker of SCD severity. Several challenges exist with regards to making the diagnosis of asthma in patients with SCD, including the high prevalence of wheezing, evidence of airway obstruction on pulmonary function testing, and/or airway hyperresponsiveness among patients with SCD. These features often occur in isolation, in the absence of other clinical criteria necessary for an asthma diagnosis. In this review we will summarize: 1) Our current understanding of the epidemiology of asthma, wheezing, airway obstruction, and airway responsiveness among patients with SCD; 2) The evidence supporting associations with SCD morbidity; 3) Our understanding of the pathophysiology of airway inflammation in SCD; 4) Current approaches to diagnosis and management of asthma in SCD; and 5) Future directions.